Pengembangan Kompetensi ASN Provinsi Kalimatan Timur Melalui Manajemen Sumber Daya Manusia Strategis - Indrawan, Jerry (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2025)
Developed countries in the world currently rely heavily on the competence of their human resources, especially state civil servants. Their progress occurred because the bureaucratic implementers, namely their civil servants, have a professional public service orientation. Unfortunately, human resources in Indonesian civil servants still need a lot of improvement, including in East Kalimantan. In fact, human resources are an integral element in an organization or institution. Institutions will not be able to develop without first developing human resources. Likewise in the context of local government, where services to local communities will not be effective and optimal without improving their human resources, in this case state civil servants. Even though the steps to develop human resources in the East Kalimantan Provincial Government have been taken, it is suspected that the results have not been optimal. Strategic human resource management is needed so that the development of the competence of the East Kalimantan Provincial Government’s state civil servants can provide excellent service to the people of East Kalimantan. For this reason, this article will provide a proposal to the East Kalimantan Provincial Government to develop the competence of its state civil servants through strategic resource management. The development of the research method used is qualitative descriptive through the search for library sources.